The leadership styles of primary healthcare center managers and center performance outcomes in Riyadh, Saudi Arabia: A correlational study - Mohammed A Alrubaysh; Mohammad H Alshehri; Eyad A Alsuhaibani; Lujain H Allowaihiq; Ammar A Alnasser; Lulu Alwazzan (Journal of Family and Community Medicine, 2022)
BACKGROUND: Leadership is a wide concept that is rapidly developing. Diverse theories suggest different styles of leadership, with strong relationships between the different styles and their outcomes. The transformational style emphasizes motivating employees and encouraging them to find new ways of dealing with issues. The transactional (TL) style promotes ideas of rewards and punishments. The Laissez–faire style is characterized by relaxation and the tendency to leave things to happen with minimal interference. MATERIALS AND METHODS: This is a descriptive cross-sectional study design conducted in Primary Healthcare Centers in Riyadh, Saudi Arabia. The leadership styles were assessed using a Multi-Factor Leadership Questionnaire, which identifies the different styles of leadership. SPSS v 26.0 was used for data analysis. t-test employed to compare leadership style between raters and managers. Logistics regression model used to determine the influence of leadership styles of managers. Pearson correlation coefficient determined the linear relationship between leadership styles and its domains. RESULTS: A total of 130 respondents (65 managers vs. 65 raters) took part. “Raters” refer to any persons other than the manager, such as a secretary, nurse, doctor. The “manager” is when the person rates himself. The global transformation mean score was 3.55, for TL it was 3.42 and for passive avoidant, the mean score was 0.93. The passive avoidant (t = 2.005; P = 0.047) and management by exception (passive) (MBEP) mean scores of raters were statistically significantly higher than managers. In the binary regression model, MBEP was the independent significant predictor of manager. CONCLUSION: The perceived leadership style of Primary Healthcare Center managers was transformational but with TL. Transformational leadership was positively correlated with TL leadership but negatively correlated with passive avoidant (The Laissez–faire style). The outcome of this study demonstrated that intellectual stimulation, idealized attributes, and inspirational motivation are perhaps better than contingent reward, active management.